Austerity, Youth Policy and the Deconstruction of the Youth Service in England - Davies, Bernard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This timely book presents a vital analysis of the politics, policy and practice of youth work services in England and the impacts of the austerity agenda introduced after the 2007-08 financial crisis. Davies frames his research within the ideological, political and economic context of the last decade, contemplating the prescriptions of neoliberalism, and various other socio-political developments. He illustrates how wider government policies, programmes and initiatives have marred the purposes and methods of the Youth Service and youth work facilities, forging connections with what this means for young people and youth work. Unique in its depth and detail, this book is one of the first comprehensive, evidenced and up-to-date accounts of UK Youth Policy. It is an essential and invaluable resource for youth educators, researchers, service managers, practitioners and activists, as well as scholars and students of youth studies, social policy, public policy, and history.
1. Mapping and Contextualising the Territory: 2007 - 2018. - Part I: THE NEW LABOUR LEGACIES -- 2. Towards a New Model of Youth Services -- 3. Practice Under Pressure: From Youth Work to 'Positive Activities' -- Part II. AUSTERITY BITES -- 4. The National Picture: From 'State Monopolies' to 'New Providers' -- 5. The Local Youth Service Experience -- Part III: WIDER YOUTH POLICY AGENDAS -- 6. Remaking 'The Broken Society' -- 7. Remoralising the Young -- 8. Parliamentary Scrutiny -- 9. Government Policy: How Positive for Youth?- PART IV: YOUTH POLICIES IN ACTION. - 10. Towards a National Service for Youth. - 11. Implementing a National Citizens Service -- 12. Youth Volunteering - The New Panacea -- 13. Plugging 'Youth Service' Gaps. - 14. Beyond the State: How 'Voluntary' Is the Voluntary Youth Sector?- PART V: TRAINING AND QUALIFYING FOR WORK WITH YOUNG PEOPLE -- 15: 'Modernising' Vocational Qualifications. - 16. Higher Education Routes in Transition- PART VI: BEYOND DECONSTRUCTION -- 17. Defending the Youth Service; Defending Youth Work. - 18. What Future for Youth Policies? What Future for the Youth Service?. .
Keywords: Family policy; Community development; Social service; Sociology; Social groups; Social history; Political planning; Children, Youth and Family Policy; Social Work and Community Development; Sociology of Family, Youth and Aging; Social History; Public Policy